A Bibliometric Analysis of Legal Approaches to Personal Data Protection - Judijanto, Loso; Solapari, Nuryati; Karauwan, Donny Eddy Sam (The Easta Journal Law and Human Rights, 2024)
This study employs bibliometric analysis to explore the expansive field of data privacy and security, utilizing data extracted from VOSviewer to identify thematic clusters, discern research trends, evaluate research opportunities, and analyze author collaboration networks. The analysis reveals several key thematic areas, including data security, legal frameworks, information privacy, and technological challenges associated with big data. These themes have evolved over time, demonstrating a shift from foundational legal principles to addressing complex technological and demographic-specific challenges, such as those related to children's data privacy. The study highlights significant concentrations of research activity as well as less explored areas that offer new opportunities for research, such as the legal status of data and specific privacy concerns that are under-represented in current literature. Furthermore, the author collaboration network provides insights into the structure of the research community, showing both dense clusters of collaboration and potential for new entrants to establish niches in emerging topics. This bibliometric perspective not only elucidates the current landscape of data privacy and security research but also points to future directions that can enhance the field's development.